Fine Grinding or Expanding as Pre-treatment for Pelleting in Processing Diets Varying in Dietary Rapeseed Expeller Proportions: Investigations on Performance, Visceral Organs, and Immunological Traits of Broilers - Liermann, Wendy; Frahm, Jana; Berk, Andreas; Böschen, Verena; Dänicke, Sven (Frontiers in Veterinary Science, 2020)
Pelleted feed is associated with improved broiler performance but also with a higher incidence of proventricular dilatation and ascites. The present study aimed to investigate influences of expanded and pelleted (ExP) or finely ground and pelleted feeds (FgP) containing either 6 % rapeseed expeller (RSE) or 12% RSE on these adverse effects by studying performance, visceral organ and immunological traits in 36 broilers. ExP reduced daily feed intake compared to FgP when feeding a 6% RSE diet (P < 0.05) but did not affect the daily feed intake when feeding a 12% RSE diet, which was also reflected in the body weight gain. There were no significant differences in the size of proventriculus and gizzard between feeding groups but significant diet-by-technical feed treatment interactions in case of proventricular and gizzard weights and the proventricular length (P < 0.05). Proventriculi and gizzards were heavier in birds fed 6%ExP than proventriculi or gizzards of animals from all other groups except for birds of the group 12%FgP. A total of three animals (1 from 6%ExP, 1 from 6%FgP and 1 from 12%ExP) developed ascites during the study. Pooled LsMeans of peripheral blood leucocyte proportions of CD3+/CD4-/CD8- cells were increased in birds fed FgP compared to birds fed ExP (P = 0.048). Pooled LsMeans of CD3+/CD4+/CD8+ T cell subsets in jejunal lamina propria were higher in birds fed 12% RSE compared to birds fed 6 % RSE (P = 0.024). Concluding, technical feed treatment or diet did not inhibit adverse effects of pelleting on gizzard and proventricular development. Morphometric alterations of proventriculus and gizzard might modify the local immune system of the distal digestive tract and promote the development of ascites; however, further studies are required to confirm this hypothesis since in the present study only 3 birds developed ascites.